2010
DOI: 10.2217/fmb.10.140
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics in The Unicellular Parasite Entamoeba Histolytica

Abstract: Amoebiasis is a serious infectious disease that is caused by the unicellular parasite, Entamoeba histolytica. This parasite is mainly found in developing countries, and are named owing to its ability to destroy tissues. The molecular mechanisms that regulate the virulence of this parasite are not well understood. In recent years, an increasing interest in the epigenetic regulation of the parasite's virulence has emerged. In this article, an overview of our current knowledge about the role of DNA methylation, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 79 publications
1
6
0
Order By: Relevance
“…Using newly generated reagents, we have identified that E. histolytica also contains this repressive epigenetic mark, which deposits at RNAi-silenced loci. Identification of a repressive H3K27Me2 suggests the presence of a functional epigenetic machinery in E. histolytica, which reinforces the identification of potential histone methyltransferases, histone modifying enzymes, DNA methylation components, and chromodomain containing proteins in the Entamoeba genome (55). Future efforts to characterize the RNA-induced transcriptional silencing complex will identify the molecular mediators of interactions between the Argonaute protein and histone modifying enzymes.…”
Section: Discussionsupporting
confidence: 54%
“…Using newly generated reagents, we have identified that E. histolytica also contains this repressive epigenetic mark, which deposits at RNAi-silenced loci. Identification of a repressive H3K27Me2 suggests the presence of a functional epigenetic machinery in E. histolytica, which reinforces the identification of potential histone methyltransferases, histone modifying enzymes, DNA methylation components, and chromodomain containing proteins in the Entamoeba genome (55). Future efforts to characterize the RNA-induced transcriptional silencing complex will identify the molecular mediators of interactions between the Argonaute protein and histone modifying enzymes.…”
Section: Discussionsupporting
confidence: 54%
“…Like other prokaryotic and viral pathogens, an intracellular protozoan parasite, Leishmania, also leads to manipulation of the host cells via epigenetic modifications of the host genome [10,38]. Epigenetics involves three main processes: DNA methylation [3], histone modification [3,4] and non-coding RNA-associated gene silencing [39].…”
Section: Discussionmentioning
confidence: 99%
“…Nutrient availability, an effective immune response and the host genetics can influence the response against pathogen challenges [ 50 52 ]; for example, it has been suggested that certain single nucleotide polymorphisms of interleukin-8 and -10 could change individual susceptibility increasing the relative risk in the development of IBS in Blastocystis carriers [ 53 ], Therefore differences for T g observed in early cultures, free of the host immune response pressure and with sufficient nutrients, allow to assume differences in the cellular protein metabolism, not yet studied between isolates recovered from symptomatic and asymptomatic carriers. Besides, some cellular and physiological features, not codified by changes in the DNA sequence, such as DNA methylation, histone modifications and RNA-associated silencing, have been associated to virulence and evasion of the immune response in some protozoan parasites, such as Entamoeba histolytica and Giardia lamblia [ 54 56 ]. Thus, many aspects of the host-pathogen relationship in Blastocystis infections require to be studied, in order to clarify the pathogenic role of this microorganism.…”
Section: Discussionmentioning
confidence: 99%